Anatomic Variations of the Right Hepatic Duct: Results and Surgical Implications from a Cadaveric Study. (29th September 2012) - Mariolis-Sapsakos, Theodoros; Kalles, Vasileios; Papatheodorou, Konstantinos; Goutas, Nikolaos; Papapanagiotou, Ioannis; Flessas, Ioannis; Kaklamanos, Ioannis; Arvanitis, Demetrios L.; Konstantinou, Evangelos; Sgantzos, Markos N.
Abstract : Purpose . Thorough understanding of biliary anatomy is required when performing surgical interventions in the hepatobiliary system. This study describes the anatomical variations of right bile ducts in terms of branching and drainage patterns, and determines their frequency. Methods . We studied 73 samples of cadaveric material, focusing on the relationship of the right anterior and posterior segmental branches, the way they form the right hepatic duct, and the main variations of their drainage pattern. Results . The anatomy of the right hepatic duct was typical in 65.75% of samples. Ectopic drainage of the right anterior duct into the common hepatic duct was found in 15.07% and triple confluence in 9.59%. Ectopic drainage of the right posterior duct into the common hepatic duct was discovered in 2.74% and ectopic drainage of the right posterior duct into the left hepatic duct in 4.11%. Ectopic drainage of the right anterior duct into the left hepatic ductal system and ectopic drainage of the right posterior duct into the cystic duct was found in 1.37%. Conclusion . The branching pattern of the right hepatic duct was atypical in 34.25% of cases. Thus, knowledge of the anatomical variations of the extrahepatic bile ducts is important in many surgical cases.